Power Control and Data Acquisition System for High Power Microwave Test Bench - 马文东 单家方 徐旵东 胡怀传 王茂 吴则格 (Plasma science & technology, 2014)
The 6 MW/4.6 GHz lower hybrid current drive （LHCD） system will be set up on the experimental advanced superconducting tokamak （EAST） for achieving a steady-state op- eration. The high power and continuous wave （CW） mode microwave test bench operating at 250 kW/4.6 GHz has already been finished, which can be used to simulate different kinds of high power microwave environments to test microwave components and units for the new LHCD sys- tem. The power control and data acquisition system on the test bench composed of power control, high reflected power protection and data acquisition function is described here in detail. Long- term operation of the test bench showed that the power control and data acquisition system is very stable and reliable.